Can a Positive Allosteric Modulation of GABAergic Receptors Improve Motor Symptoms in Patients with Parkinson’s Disease? The Potential Role of Zolpidem in the Treatment of Parkinson’s Disease - Antonio Daniele; Francesco Panza; Antonio Greco; Giancarlo Logroscino; Davide Seripa (Parkinson's Disease)
At present, patients with advanced Parkinson’s disease (PD) are unsatisfactorily controlled by currently used anti-Parkinsonian dopaminergic drugs. Various studies suggest that therapeutic strategies based on nondopaminergic drugs might be helpful in PD. Zolpidem, an imidazopyridine widely used as sleep inducer, shows high affinity only for GABAA receptors containing the α-1 subunit and facilitates GABAergic neurotransmission through a positive allosteric modulation of GABAA receptors. Various observations, although preliminary, consistently suggest that in PD patients zolpidem may induce beneficial (and sometimes remarkable) effects on motor symptoms even after single doses and may also improve dyskinesias. Since a high density of zolpidem binding sites is in the two main output structures of the basal ganglia which are abnormally overactive in PD (internal globus pallidus, GPi, and substantia nigra pars reticulata, SNr), it was hypothesized that in PD patients zolpidem may induce through GABAA receptors an inhibition of GPi and SNr (and, possibly, of the subthalamic nucleus also), resulting in an increased activity of motor cortical areas (such as supplementary motor area), which may give rise to improvement of motor symptoms of PD. Randomized clinical trials are needed in order to assess the efficacy, safety, and tolerability of zolpidem in treating motor symptoms of PD.